Combating malnutrition: time to act - Gillespie, Stuart; McLachlan, Milla; Shrimpton, Roger (World Bank, 2003)
The book illustrates the constraints that have limited action towards improving nutrition in the developing world. The understanding of how to best promote the needed changes in policies, programs, and institutional capacities has grown over the past decade, but remains limited. The international community has systemized its knowledge of what actions are likely to improve nutrition, but less effort to systemizing its knowledge of how to intervene in the sociopolitical processes---from community to national and international levels. The assessment recommends a five-point program of action to apply to known solutions with the intensity needed to eliminate nutritional deprivation. Each dimension of the program is an entry point; while local conditions and existing capacity will determine which one is most appropriate in any one context, ultimately all five dimensions need action for maximum impact. The book concludes that UNICEF and the World Bank, with their complementary approaches and in partnership with countries and other agencies, should initiate a global effort to jump-start action to eliminate nutritional deprivation once and for all.